Radioscapholunate fusion under wide awake surgery - Nur Azree Ferdaus, Kamudin; Amir Adham, Ahmad; Shalimar, Abdullah (2019)
Objectives / Interrogation: Scaphoid-non-union-advance collapse (SNAC) or scapholunate-advance collapse (SLAC) is one of the associated conditions following neglected unstable scaphoid fracture. Surgical treatment for degenerative joint disease of the radioscapholunate joint is arthrodesis. We document a radioscapholunate fusion done under wide awake surgery. The reason was due to limited general anaesthetic time. A 39-year-old-male sustained a motor vehicle accident and fell onto his outstretched right hand. Three months later he presented with worsening right wrist pain and limited range of motion for the past 3 months. He initially did not seek treatment as he thought it was just a sprain until his wrist pain had worsened considerably. Methods: The RSL joint arthrodesis was done under local anesthesia using the "Walant" technique, also known as "wide-awake-local-anesthesia-no-tourniquet". Tumescent anesthesia technique was used to infiltrate the surrounding surgical field. Four different regions were injected with 10cc of anaesthetic solution beginning from 1) the subcutaneous area over the incision site surrounding the dorsal area of the wrist, 2) subperiosteally to the distal radius, 3) into the radial-scaphoid-lunate joint and 4) surrounding the carpal region. The solution comprised of normal saline, lignocaine, sodium bicarbonate and adrenaline with the adrenaline at a diluted strength of 1:100 000. Results and Conclusions: The surgery was successfully completed within 1.5 hours with a NPRS (numerical pain rating score) of 0/10. There was no requirement for top-up injection. Thus, it is possible to utilize wide-awake-local-anesthesia-no-tourniquet (walant) for limited wrist fusion such as in RSL arthrodesis. As this is an elective surgery, it can be done earlier under daycare surgery saving potential cost for the patient and providing earlier pain relief.